Spasticity Effect in Cerebral Palsy Gait - Rosa, Marlene (2018)
A high number of children with cerebral palsy (CP) have spastic gait and consequently abnormalities in joint patterns. Several factors have been contributing to the lack of consensus on the spasticity effect in cerebral palsy gait and would be summarized and discussed in this chapter, e.g., spastic gait patterns are in constant evolution during the process of growth; there are still considerable limitations in the methodologies used to assess spasticity during gait; a wide range of rehabilitation strategies have been explored to control spasticity during gait. Spastic gait patterns are divided in hemiplegic (5 types) and diplegic (4 types) with the most prevalent joint abnormalities described in the sagittal plane. Ashworth, Tardieu, and DAROM scales and Pendulum Tests are widely used to assess spasticity but do not reliably explain the spasticity effects during gait. Orthotics, adequate exercise or handling techniques, botulinum injections, or surgical procedures have been used to manage spasticity effects.